ТНЕ WORLD OIL MARKET: THE SEARCH FOR BALANCE IN THE NEW "OIL" REALITY - T. A. Malova; V. I. Sisoeva (Vestnik MGIMO-Universiteta)
The article provides an analysis of change of the world oil market in the face of new "oil" reality. Factors of formation of new "oil" reality in the global world defined. Scientific background and current state of research of the problem are described. It is shownthat in the Russian and foreign literature the considerable attention is paid to the analysis of dynamics of the quantitative variables characterizing fluctuations and shocks in the oil market. At the same time the search for balance in the new "oil" reality are not considerably investigated yet. The proposed approach allows toreveal the substance of the transformation of the world oil market, to assess the changes in the oil market with the development of rhenium in terms of efficiency and functioning of the mechanism, the prospects of price volatility in the oil market. The main directions of transformation of the oil market are follows. Development of a subject basis of the oil market due to changes of a role of the main market players whose structure includes the USA, Saudi Arabia, Russia now. The impact of regulatory factors complex in the oil market towards equilibrium, which include activity of OPEC, supply of shale oil, future market,activity of the uniform regulator and national regulators. Transformation of the oil market in the direction of perfection of the competitive relations, achievement of optimum market balance as a result of coordination and interaction of interests of participants of the global oil market.